Investigating the effect of brain break exercise videos on mental stress, personality, mental hardiness, social support and physical activity among college students in Jiangxi province, China - Mingzhu, Pan (2025)
College students, as a distinct cohort, are navigating the transition between campus and social life, facing pressures such as interpersonal dynamics, academic demands, financial constraints, employment expectations, and daily stress. Managing psychological well-being in universities is a pressing concern. Engaging in physical activity, such as Brain Breaks exercise videos, has been shown to have a positive impact on mental health by reducing stress levels. This study primarily aims to validate the uBioMacpa Pro stress measurement tool among Chinese college students. Studies indicated that individual characteristics like personality traits, hardiness, social support, and physical activity profoundly influence mental stress levels. Thus, the subsequent objectives were to explore the relationships between these factors and mental stress, and to evaluate the effect of Brain-breaks exercise video intervention on the study variables among Chinese college students in Shangrao City, Jiangxi Province. The study was conducted in two phases, Phase 1 involved reliability and validity tests of the uBioMacpa Pro and a cross-sectional study, with 60 students involved in the reliability test, 200 in the validity test, and 890 in the cross-sectional study. Additionally, 80 students with mental stress from Phase 1 participated in Phase 2, which was a randomized controlled trial. In phase 2, 80 students were randomly College students, as a distinct cohort, are navigating the transition between campus and social life, facing pressures such as interpersonal dynamics, academic demands, financial constraints, employment expectations, and daily stress. Managing psychological well-being in universities is a pressing concern. Engaging in physical activity, such as Brain Breaks exercise videos, has been shown to have a positive impact on mental health by reducing stress levels. This study primarily aims to validate the uBioMacpa Pro stress measurement tool among Chinese college students. Studies indicated that individual characteristics like personality traits, hardiness, social support, and physical activity profoundly influence mental stress levels. Thus, the subsequent objectives were to explore the relationships between these factors and mental stress, and to evaluate the effect of Brain-breaks exercise video intervention on the study variables among Chinese college students in Shangrao City, Jiangxi Province. The study was conducted in two phases, Phase 1 involved reliability and validity tests of the uBioMacpa Pro and a cross-sectional study, with 60 students involved in the reliability test, 200 in the validity test, and 890 in the cross-sectional study. Additionally, 80 students with mental stress from Phase 1 participated in Phase 2, which was a randomized controlled trial. In phase 2, 80 students were randomly